A method for evaluating the performance of glued laminated wood

By establishing the response relationship between the mechanical properties of glued wood and the number of layers in different tree species, the problems of waste of materials, high costs and low representative results in the mechanical properties evaluation of glued wood are solved, and the cost and experimental difficulty of the evaluation are reduced, which improves the accuracy and convenience of the evaluation.

CN115356217BActive Publication Date: 2025-03-18INNER MONGOLIA AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210695942.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-20
Publication Date
2025-03-18
Estimated Expiration
2042-06-20

AI Technical Summary

Technical Problem

The prior art has problems such as waste of materials, high cost, high experimental difficulty and low representative results in the evaluation of mechanical properties of glued wood, especially in the evaluation of bending and shear resistance.

Method used

By establishing the response relationship between the mechanical properties and the number of layers of glued wood in different tree species, the mechanical properties of multi-layer laminated wood are calculated using specific functional relationships, reducing the experimental difficulty and cost, and improving the accuracy and representativeness of the evaluation.

Benefits of technology

The cost and experimental difficulty of the evaluation of the mechanical properties of glued wood are reduced, and the accuracy and convenience of evaluation are improved. They are suitable for the same laminated glued wood and are closer to the mechanical properties of actual glued wood.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115356217B_ABST
    Figure CN115356217B_ABST
Patent Text Reader

Abstract

A method for evaluating the mechanical properties of glued laminated timber is an evaluation method for the mechanical properties of glued laminated timber with the same combination of plies. The bending performance test in the mechanical property evaluation of glued laminated timber is often carried out to determine the strength grade of the glued laminated timber through full-scale test of glued laminated timber components. The full-scale component destruction test wastes the raw materials of glued laminated timber, is costly, has high requirements on the testing equipment, and is difficult to test. Another method is to calculate the bending strength of glued laminated timber through the tensile strength of the plies, but such a calculation method does not distinguish between the tree species used, and has problems such as low representativeness of the results. In the shear performance evaluation experiment, the evaluation index comes from the plies of each strength grade at the middle two-thirds of the component cross section, and the shear strength of the small material test piece along the grain is used as the shear strength of the glued laminated timber. The shear strength value of the small shear test piece is several times higher than the shear failure strength of the large-size wood structure components used in actual engineering applications, so it is inaccurate to directly apply it to actual engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of glulam performance testing, and in particular to a glulam performance evaluation method. Background Art

[0002] Glued laminated timber is an environmentally friendly engineering composite wood with a high strength-to-weight ratio. As a green building material that integrates modern scientific and technological elements, it has been widely used in various engineering fields. Although wood is a renewable resource, it takes hundreds of years to accumulate high-quality wood. At present, more than 95% of my country's wood structure enterprises are small and medium-sized enterprises. In the manufacture and utilization of glued laminated timber components, the lack of reference specifications or the lack of understanding of the mechanism of its mechanical properties will lead to waste of good materials, such as using inferior materials and large materials for small purposes. Therefore, in order to make the best use of glued laminated timber, it is necessary to obtain the mechanical strength of the produced glued laminated timber more accurately, so that the value of each piece of material can be fully utilized in practical applications. How to accurately evaluate the mechanical properties of glued laminated wood is of great significance to improving the performance of glued laminated wood and increasing the utilization rate of the board. There is no relevant system for the research on the lamination effect and size effect of glued laminated wood. Due to factors such as the anisotropy of wood, the accumulation of layers does not necessarily result in a single increase in mechanical properties. In actual construction, inaccurate evaluation of the mechanical properties of glued laminated wood of different tree species will cause material waste and even safety problems. Therefore, it is particularly important to establish a mechanical property evaluation system for glued laminated wood of various common tree species to provide a reference for selecting the most economical component combination in actual projects and solve the problem that the strength of glued laminated wood is not fully utilized in actual use.

[0003] Laminated glulam is made of stress-graded logs or sawn timber as the main material (thickness 20-45mm), with a moisture content not exceeding 18%. After planing, it is layered, bonded and pressurized with high-performance environmentally friendly adhesives. Equal-combination glulam refers to glulam components that are composed only of lamellas of the same material grade.

[0004] (1) In the GB / T50708Y-2012 Technical Specification for Glued Laminated Timber Structures, the strength grade of glued laminated timber is determined by full-scale component tests. The test is conducted using glued laminated timber with a cross-sectional height of 300 mm. In the bending test, there are no less than 2 groups of representative glued laminated timber components, and each group has no less than 15 specimens. Such full-scale component destruction tests have the problems of waste of glued laminated timber materials, high experimental costs, high requirements for testing equipment, high experimental difficulty, and low representativeness of the obtained strength results due to the neglect of the number of glue layers in the full-scale specimens. Another method is to use the tensile strength value of the same glued laminated timber ply to calculate the bending strength value of the glued laminated timber. However, this calculation method does not distinguish between the tree species used, and has the problem of low representativeness of the results.

[0005] (2) In the shear test, the representative wood specimens were selected from the plywood of each strength grade at the middle two-thirds of the cross section of the member, and ten specimens were selected for each plywood grade. This method is a domestic standard taken from the American standard ASTM D245, and its value is taken from the shear test of small specimens along the grain (ASTM1995A). It is reported that the shear strength value of the small shear specimen is several times higher than the shear failure strength of large-sized wood structural components used in actual engineering applications, so it is inaccurate to directly apply it to actual engineering.

[0006] In the experimental example of Larix glulam, it was found that there was a good linear fitting function between the bending mechanical properties, shear mechanical properties and the number of layers of the glued laminated timber. Therefore, the evaluation method proposed in the present invention is to infer the mechanical properties of glued laminated timber with different numbers of layers based on a specific function between the number of layers. The method of the present invention only needs to conduct tests on different tree species to establish evaluation standards to provide a calculation method for the evaluation of the mechanical properties of glued laminated timber in actual production.

[0007] Disadvantages of existing technology

[0008] (1) The mechanical properties of glulam are often evaluated by full-scale tests on glulam components to determine the strength grade of glulam. Full-scale component failure tests waste glulam materials, are costly, require high testing equipment, and are difficult to test. Another method is to calculate the bending strength of glulam by the tensile strength of the plywood. However, this calculation method does not distinguish between the tree species used and has problems such as low representativeness of the results.

[0009] (2) The evaluation index of the shear test comes from the plywood of each strength grade at the middle two-thirds of the component cross section. The shear strength along the grain of the small material test piece is used as the shear strength of the glued laminated timber. However, the shear strength value of the small shear test piece is several times higher than the shear failure strength of the large-sized wood structure components used in actual engineering applications. Therefore, it is inaccurate to directly apply it to actual engineering. Summary of the invention

[0010] In order to solve the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a method for evaluating the mechanical properties of glued laminated timber, establish an evaluation system for glued laminated timber of different tree species, reduce experimental difficulty and cost, and improve accuracy and convenience.

[0011] To achieve the above object, the technical solution of the present invention is:

[0012] A method for evaluating the mechanical properties of glued laminated wood includes the following two tests:

[0013] Bending test

[0014] Select the plywood used in the production of the same glulam in a certain production batch and make test specimens according to a certain size;

[0015] The four-point bending loading method is adopted.

[0016] At the mid-span position of the beam, strain gauges are arranged at equal height intervals, and displacement meters are installed at the three points and mid-span of the beam to collect the strain and displacement of the component. After loading is completed and the specimen is broken, samples are taken around the failure position to determine that the moisture content is still between 8% and 12%;

[0017] The ultimate bending moment of the glued laminated timber is measured experimentally: Among them, M is the ultimate bending moment; P is the ultimate load; L is the span. The relationship between the ultimate bending moment M of the glulam bending test and the number of layers n is analyzed. Through regression analysis, the curve equation of the relationship between the ultimate bending moment of glulam and the number of layers is obtained. If you want to know the bending strength of a certain number of layers of glulam, you only need to enter the value of the number of layers n to calculate the ultimate bending moment, and then use the bending strength formula b is the cross-section width; h is the cross-section height. The bending strength of a certain number of layers of glued laminated wood is calculated to determine the strength grade of this glued laminated wood;

[0018] Shear test

[0019] Select the plywood used in the production of the same glued laminated wood batch to make the test specimens;

[0020] The shear performance test adopts three-point bending method and five-point bending method to load. A displacement meter is installed at each loading point, and a strain gauge is pasted at the bottom of the beam at the loading point. A vertical strain gauge is pasted at 5h / 8 away from the support point to measure the longitudinal shear stress. Three strain rosettes at a 45-degree angle are pasted at the loading point and the middle of the support point to measure the shear strain at the point. The deflection and strain are synchronously collected by static strain gauges.

[0021] Make a 20×20mm grid line on the side of the beam. When the vertical marking line is broken, the loading is completed. After the specimen is broken, samples are taken around the failure position. The moisture content is still between 9% and 12%;

[0022] The failure shear force of glued laminated wood is measured by experiment, and then the formula is used τ is shear strength; P is load; b is section width; h is section height. The shear strength is calculated, and the relationship between the shear strength and the number of layers of the glulam shear test is analyzed. Through regression analysis, the curve equation of the shear strength and the number of layers of the glulam of Scotch pine is obtained.

[0023] If you want to know the shear strength of a certain number of plies of glued laminated wood, you only need to enter the value of the number of plies n to calculate the shear strength and determine the strength grade of this glued laminated wood.

[0024] Furthermore, in the bending test, the loading equipment is a hydraulic jack with a maximum test force of 20t. The loading method adopts step-by-step loading. Since the ultimate load of a single-layer plate is small, the single layer of the plate is loaded at 0.5KN as a level, and the other layers are loaded at 1KN as a level. Loading is stopped when the specimen is severely damaged.

[0025] Furthermore, in the bending test, steel gaskets are arranged at the loading points to transfer the load on the distribution beam.

[0026] Furthermore, the curve equation of the relationship between the ultimate bending moment of the glued laminated timber and the number of layers in the bending test is: M = 0.7255n 2 -1.6557n+1.5734

[0027] Where M is the ultimate bending moment (KN·m), n is the number of plies of glulam, and the coefficient of determination R2 of the relationship between the ultimate bending moment and the number of plies is 0.9929. Through this relationship, the ultimate bending moment of a single ply can be used to estimate the ultimate bending moment of Larix glulam with the same combination of different plies.

[0028] Furthermore, in the shear test, the loading equipment is a 20t hydraulic jack, and the test is carried out in a step-by-step loading manner with 2KN as one level. Loading is stopped when the bearing capacity of the specimen drops to 80% of the ultimate load or the specimen shows obvious shear failure. The failure load of the shear test is relatively large. In order to avoid transverse compression failure near the loading point, a steel pad is added at the loading point and the support point so that the transverse compression stress does not exceed 7Mpa.

[0029] Furthermore, the curve equation of the shear strength and layer number response relationship in the shear test is:

[0030] τ=7.3428n -0.464

[0031] In the formula, τ is the shear strength (MPa), n is the number of glulam layers, and the determination coefficient R2 of the relationship between shear strength and number of layers is 0.9801. Through this relationship, the shear strength of the single layer can be used to estimate the shear strength of Larix glulam with the same combination of different numbers of layers.

[0032] Compared with the prior art, the beneficial effects of the present invention are:

[0033] The present invention is an evaluation method for the mechanical properties of glulam with equal combination of plies. The bending performance test in the mechanical property evaluation of glulam is often carried out to determine the strength grade of glulam through full-scale test of glulam components. The full-scale component destruction test wastes glulam materials, has high cost, high requirements for test equipment, and great experimental difficulty. Another method is to calculate the bending strength of glulam by the tensile strength of the plies, but such a calculation method does not distinguish between the tree species used, and has the problem of low representativeness of the results. In the shear performance evaluation experiment, the evaluation index comes from the plies of each strength grade at the middle two-thirds of the component cross section, and the shear strength along the grain of the small material test piece is used as the shear strength of the glulam. The shear strength value of the small shear test piece is several times higher than the shear failure strength of the large-size wood structure component used in actual engineering applications. Therefore, it is inaccurate to directly apply it to actual engineering.

[0034] To address these issues, the evaluation method proposed in the present invention is to establish a mechanical property layer response mechanism for different tree species according to this method, and to determine the strength grade of glued timber by inferring the mechanical properties of multi-layer ply glued timber through a specific functional relationship. This reduces the cost of evaluating the mechanical property grade of glued timber, and makes evaluation of different tree species more convenient and representative in practical applications.

[0035] The evaluation method of this invention is applicable to glulam with equal ply, but not to glulam with different ply or other glulam.

[0036] The bending test requires a span-to-height ratio greater than 18 to achieve bending failure effect, and the shear test requires a shear span ratio less than 2.5 to achieve shear failure effect.

[0037] This invention can reduce the amount of experiments for evaluating the grade of glued laminated wood. During factory inspection and in specific construction, the mechanical property grade of glued laminated wood can be estimated based on the mechanical property parameters of the provided laminated wood.

[0038] For the shear performance test, the existing situation of using the shear strength of small specimens along the grain as the shear strength of glued wood is changed, and the method of the present invention is closer to the actual shear strength of glued wood;

[0039] This evaluation method will conduct corresponding experiments on various tree species, and establish a mechanical relationship function between various tree species and the number of layers of glued laminated timber based on this invention method as a new type of glued laminated timber grade evaluation method.

[0040] The evaluation method proposed in the present invention does not require a large number of full-scale specimen experiments in bending tests. The relationship between the bending performance of equal glued laminated timber and the number of layers can be obtained by data analysis through bending tests on glued laminated timber with different numbers of layers. The destructive experiment has low cost and low difficulty. A complete evaluation system for the relationship between the mechanical properties of glued laminated timber is established for different tree species, which is more targeted and greatly improves convenience.

[0041] The evaluation method proposed in the present invention is used in shear tests. The evaluation index of traditional shear tests comes from the plies of each strength grade at the middle two-thirds of the component cross section. The shear strength along the grain of the small material test piece is used as the shear strength of the glued laminated wood. The shear strength value of the small shear test piece is several times higher than the shear failure strength of the large-size wooden structural components used in actual engineering applications. Therefore, it is inaccurate to directly apply it to actual engineering. The evaluation method of the present invention can obtain the shear strength of glued laminated wood with a certain number of layers through a specific function, which is more accurate. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is the loading device diagram for the bending test;

[0043] Figure 2 This is the loading device diagram of the three-point bending method for shear test;

[0044] Figure 3 This is the diagram of the loading device for the five-point bending method for shear test;

[0045] Figure 4 is the ultimate bending moment-story number response fitting curve;

[0046] Figure 5 Fitting curve of glulam shear strength-glulam layer number response function. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments:

[0048] like Figure 1-5 As shown, a method for evaluating the mechanical properties of glued laminated wood includes the following two tests:

[0049] 1 Bending test

[0050] The test specimens were made by selecting the plywood used in the production of the same glued laminated wood in a certain production batch (the example experiment used Pinus sylvestris var. mongolica) as follows:

[0051]

[0052] (W1C means bending test 1 layer specimen, W2C means bending test 2 layers specimen...)

[0053] The thickness of glulam plies is generally required to be no less than 20mm and no more than 45mm. In actual application research, the commonly used ply thickness specification of glulam beams is 25mm, which accounts for the largest proportion. Therefore, 25mm is selected as the unit size for the bending test, and the thickness parameter is converted into the number of layers parameter for testing.

[0054] The bending performance test adopts a four-point bending loading method. The loading equipment is a hydraulic jack with a maximum test force of 20t. The loading method adopts step-by-step loading. Since the ultimate load of a single-layer plate is small, the single layer of the plate is loaded at 0.5KN as a first level, and the other layers are loaded at 1KN as a first level. Loading is stopped when the specimen is severely damaged.

[0055] Steel gaskets are set at the loading points to transfer the load on the distribution beam. At the mid-span of the beam, strain gauges are arranged at equal height intervals, and displacement meters are installed at the three-point points and mid-span of the beam. The strain and displacement of the component are collected synchronously using the Donghua Testing DH3818 static strain gauge. After the loading is completed and the specimen is broken, samples are taken around the broken position. According to the method specified in "Structural Integrated Timber" (GB / T2699-2011), the moisture content is still between 9% and 12%.

[0056] The four-point bending method is used to carry out the bending test of glulam, and the ultimate bending moment of glulam laminate is measured through the experiment.

[0057] (M is the ultimate bending moment; P is the ultimate load; L is the span), analyze the relationship between the ultimate bending moment M of the glulam bending test and the number of layers n, and obtain the curve equation of the relationship between the ultimate bending moment of glulam and the number of layers through regression analysis. If you want to know the bending strength of a certain number of layers of glulam, you only need to enter the value of the number of layers n to calculate the ultimate bending moment, and then use the bending strength formula (b is the section width; h is the section height), calculate the bending strength of a certain number of layers of glued laminated timber to determine the strength grade of this glued laminated timber.

[0058] 2 Shear test

[0059] The test specimens were selected from a batch of the same glued laminated wood (the example experiment used Pinus sylvestris var. mongolica) to make the following:

[0060]

[0061] (J1C is interpreted as a shear test specimen with 1 layer, J2C is interpreted as a shear test specimen with 2 layers...)

[0062] Since the shear span ratio of the shear test is set to 2.5, the specimen size is small when the layer plate unit thickness is 25mm. The experimental equipment used in the example is limited by the test span. Therefore, 35mm is selected as the unit size (the thickness unit that is more widely used in actual applications), and the thickness parameter is converted into the number of layers parameter for testing.

[0063] The shear performance test adopts three-point bending method and five-point bending method to load. A displacement meter is installed at each loading point, and a strain gauge is pasted on the bottom of the beam at the loading point. A vertical strain gauge is pasted at 5h / 8 away from the support point to measure the longitudinal shear stress. Three strain rosettes at a 45-degree angle are pasted at the loading point and the middle of the support point to measure the shear strain at the point. The deflection and strain are synchronously collected using static strain gauges.

[0064] The loading equipment is a 20t hydraulic jack. The test is carried out in a step-by-step loading manner with 2KN as one level. Loading is stopped when the bearing capacity of the specimen drops to 80% of the ultimate load or the specimen shows obvious shear failure. The failure load of the shear test is large. In order to avoid transverse compression failure near the loading point, a steel pad is added at the loading point and the supporting point respectively so that the transverse compression stress does not exceed 7Mpa.

[0065] In order to better observe the shear failure characteristics of the test beam, a 20×20mm grid line is made on the side of the beam. When the vertical marking line is broken, it means that longitudinal shear failure has occurred. After the loading is completed and the specimen is broken, samples are taken around the failure position. According to the method specified in "Structural Integrated Timber" (GB / T2699-2011), the moisture content is still between 9% and 12%.

[0066] The failure shear force of glued laminated wood is measured by experiment, and then the formula is used (τ is shear strength; P is load; b is section width; h is section height) to calculate the shear strength, analyze the relationship between the shear strength of glued laminated timber and the number of layers in the shear test, and obtain the curve equation of the shear strength and number of layers response relationship of Larix glulam through regression analysis. If you want to know the shear strength of a certain number of layers of glued laminated timber, you only need to substitute the value of the number of layers n to calculate the shear strength and determine the strength grade of this glued laminated timber.

[0067] In the experimental example of Pinus sylvestris glulam, it was found that there was a good linear fitting function between the bending mechanical properties and shear mechanical properties of glulam and the number of layers. Therefore, the evaluation method proposed in the present invention is to use the relationship between the mechanical properties of glulam and the number of layers to infer the mechanical properties of glulam with different numbers of layers for evaluation.

[0068] (1) Example of bending test on Pinus sylvestris glued laminated timber

[0069] Bending test specimen parameters

[0070]

[0071] Bending test results table

[0072]

[0073] The example test analyzed the relationship between the ultimate bending moment and the number of layers of the flexural test of Pinus sylvestris glulam. Through regression analysis, the curve equation of the relationship between the ultimate bending moment and the number of layers of Pinus sylvestris glulam was obtained.

[0074] M=0.7255n 2 -1.6557n+1.5734

[0075] Where M is the ultimate bending moment (KN m), n is the number of plies of glulam, and the determination coefficient R2 of the relationship between the ultimate bending moment and the number of plies is 0.9929. Based on this relationship, the ultimate bending moment of a single ply can be used to estimate the ultimate bending moment of Larix glulam with the same combination of different plies.

[0076] (2) Example of shear test on Pinus sylvestris glued laminated timber

[0077] Shear test specimen parameter table

[0078]

[0079] Shear test results table

[0080]

[0081] The example test analyzed the relationship between the shear strength of Pinus sylvestris glued laminated timber and the number of layers. Through regression analysis, the curve equation of the response relationship between the shear strength of Pinus sylvestris glued laminated timber and the number of layers was obtained.

[0082] τ=7.3428n -0.464

[0083] In the formula, τ is the shear strength (MPa), n is the number of plies of glulam, and the determination coefficient R2 of the relationship between shear strength and number of plies is 0.9801. Through this relationship, the shear strength of the single ply can be used to estimate the shear strength of Larix glulam with the same combination of different plies.

[0084] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that are not conceived through creative work should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined in the claims.

Claims

1. A method for evaluating the mechanical properties of glued wood, characterized by: The test consists of two parts: Bending test Select the plywood used in the production of the same glued laminated wood in a certain production batch and make test specimens according to a certain size. The difference in moisture content between adjacent plywood layers shall not exceed 3%; The four-point bending loading method is adopted. At the mid-span position of the beam, strain gauges are arranged at equal height intervals, and displacement meters are installed at the three points and mid-span of the beam to collect the strain and displacement of the component. After loading is completed and the specimen is broken, samples are taken around the broken position to determine the moisture content, which is still between 8% and 12%; The ultimate bending moment of glued laminated timber is measured experimentally: Among them, M is the ultimate bending moment; P is the ultimate load; L is the span. The relationship between the ultimate bending moment M of the glulam bending test and the number of layers n is analyzed. Through regression analysis, the curve equation of the relationship between the ultimate bending moment of glulam and the number of layers is obtained. If you want to know the bending strength of a certain number of layers of glulam, you only need to enter the value of the number of layers n to calculate the ultimate bending moment, and then use the bending strength formula b is the section width; h is the section height, W is the section modulus, and the bending strength of a certain number of plies of glulam is calculated to determine the strength grade of this glulam; Shear test The moisture content difference between adjacent plywood sheets used in the production of the same glued laminated wood in a certain production batch shall not exceed 3%; The shear performance test adopts three-point bending method and five-point bending method to load. A displacement meter is installed at each loading point, and a strain gauge is pasted at the bottom of the beam at the loading point. A vertical strain gauge is pasted at 5h / 8 away from the support point to measure the longitudinal shear stress. Three strain rosettes at a 45-degree angle are pasted at the loading point and the middle of the support point to measure the shear strain at the point. The deflection and strain are synchronously collected by static strain gauges. Make a 20×20mm grid line on the side of the beam. When the vertical marking line is broken, the loading is completed. After the specimen is broken, samples are taken around the failure position. The moisture content is still between 8% and 12%; The failure shear force of glued laminated wood is measured by experiment, and then the formula is used τ is shear strength; P is load; b is section width; h is section height. The shear strength is calculated, and the relationship between the shear strength and the number of layers of the glulam shear test is analyzed. Through regression analysis, the curve equation of the shear strength and the number of layers of the glulam of Scotch pine is obtained. If you want to know the shear strength of a certain number of plies of glulam, you only need to enter the value of the number of plies n to calculate the shear strength and determine the strength grade of this glulam. The curve equation of the relationship between the ultimate bending moment of the glued laminated timber and the number of layers in the bending test is: M = 0.7255n 2 -1.6557n+1.5734 Where M is the ultimate bending moment (KN·m), n is the number of plies of glulam, and the coefficient of determination R2 of the relationship between the ultimate bending moment and the number of plies is 0.9929. Through this relationship, the ultimate bending moment of the single ply can be used to estimate the ultimate bending moment of Pinus sylvestris glulam with the same combination of different plies; The curve equation of the relationship between shear strength and number of layers in the shear test is: τ=7.3428n -0.464 Where τ is the shear strength (MPa), n is the number of plies of glulam, and the determination coefficient R2 of the shear strength and number of plies relationship curve is 0.9801. Through this relationship, the shear strength of the single ply can be used to estimate the shear strength of Larix glulam with the same combination of different plies.

2. The method according to claim 1, characterized in that: In the bending test, the loading equipment is a hydraulic jack with a maximum test force of 20t. The loading method adopts step-by-step loading. Since the ultimate load of a single-layer plate is small, the single layer of the plate is loaded at 0.5KN as a level, and the other layers are loaded at 1KN as a level. Loading is stopped when the specimen is severely damaged.

3. The method according to claim 1, characterized in that: In the bending test, steel spacers are arranged at the loading points to transfer the load on the distribution beam.

4. The method according to claim 1, characterized in that: In the shear test, the loading equipment is a 20t hydraulic jack, and the test is carried out in a step-by-step loading manner with 2KN as one level. Loading is stopped when the bearing capacity of the specimen drops to 80% of the ultimate load or the specimen shows obvious shear failure. The failure load of the shear test is relatively large. In order to avoid transverse compression failure near the loading point, a steel pad is added at the loading point and the supporting point respectively, so that the transverse compression stress does not exceed 7Mpa.